O ensino colaborativo como propulsor para o processo de identificação de estudantes com indicadores de altas habilidades/superdotação - Silva, Patricia Santos da (2023)
One of the great challenges facing schools is the effective inclusion of all students, and collaborative teaching (CT) has emerged as a practice that facilitates this process. Thus, the question that drives this research is how can collaborative teaching reverberate in strategies for identifying students with high abilities/ giftedness (HA/G)? This qualitative study aimed to identify collaborative teaching experiences among teachers in Specialized Educational Assistance (SEA) and regular education, exploring their implications for identifying students with HA/G. And the specific objectives were: a) Identify teachers experiences related to high abilities/giftedness; b) To analyse the factors that influenced the context of collaborative practices between SEA and regular class teachers; c) To identify how school management acts in the context of collaborative practices in the school. d) To promote training among teachers in the municipal network on the subject of CT and HA/G and to prepare training material with 'clues' for organizing CT practices from the perspective of identifying students with indicators of HA/G. Nine teachers from the Municipal Network of Santa Maria/RS took part in this research, who had been nominated by the Municipal Department of Education (SMEd) because they work on initiatives involving CT practices. The group included three special education teachers, three regular education teachers and three managing teachers. This study used semistructured interviews as a data collection tool, recorded via Meet. We opted for Bardin's Thematic Content Analysis (2016). In analyzing the data, we used guiding concepts such as 'High Abilities/Gifted' (RENZULLI, 2021), 'Identification' (FREITAS E PEREZ, 2012; VIEIRA, 2005), and 'CT' (MENDES, VILARONGA E ZERBATO, 2023), which are in line with the theoretical framework under which the data was discussed. The results showed that CT is a driver for identifying students with indicators of HA/G. However, there is still a need for continuing training on these issues for all teachers. It was clear that the schools involved, represented by the participating teachers, are on a journey towards an inclusive school, at different times, in different contexts and with different knowledge. They are all engaged and receptive to new practices and continuing training on CT and on improving the identification of students with indicators of HA/G. In this sense, the professional master's degree product of this research was the organization of a round table discussion between teachers from the Municipal Education Network on HA/G and CT and the production of a training leaflet, ‘Clues’: CT - A look at High Abilities/Giftedness), to encourage the development of CT practices from the perspective of identifying students with indicators of HA/G. This material was sent to all the schools in the Municipal Education Network of Santa Maria/RS.